2023
DOI: 10.1021/acs.jpclett.3c03062
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in Organic Electrochemical Transistors: Distinction of Capacitive and Inductive Effects

Juan Bisquert

Abstract: Organic electrochemical transistors (OECTs) are effective devices for neuromorphic applications, bioelectronics, and sensors. Numerous reports in the literature show persistent dynamical hysteresis effects in the current–voltage curves, attributed to the slow ionic charging of the channel under the applied gate voltage. Here we present a model that considers the dominant electrical and electrochemical operation aspects of the device based on a thermodynamic function of ion insertion. We identify the volume cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 58 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…Despite these insights, few device models have comprehensively accounted for these factors in describing OECTs hysteresis phenomena. Bisquert et al identified four distinct relaxation phenomena that contributing to the complex dynamics of hysteresis in OECTs: time constants related to electronic and ionic currents, vertical and lateral ion diffusion, and the effects of electrolyte resistance and film capacitance [ 54 ]. They also distinguish between capacitive and inductive hysteresis, associated with ion diffusion in the organic film, which manifest as counterclockwise and clockwise loops, respectively, in the transfer current [ 54 ].…”
Section: Working Principle Of Oectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these insights, few device models have comprehensively accounted for these factors in describing OECTs hysteresis phenomena. Bisquert et al identified four distinct relaxation phenomena that contributing to the complex dynamics of hysteresis in OECTs: time constants related to electronic and ionic currents, vertical and lateral ion diffusion, and the effects of electrolyte resistance and film capacitance [ 54 ]. They also distinguish between capacitive and inductive hysteresis, associated with ion diffusion in the organic film, which manifest as counterclockwise and clockwise loops, respectively, in the transfer current [ 54 ].…”
Section: Working Principle Of Oectsmentioning
confidence: 99%
“…Bisquert et al identified four distinct relaxation phenomena that contributing to the complex dynamics of hysteresis in OECTs: time constants related to electronic and ionic currents, vertical and lateral ion diffusion, and the effects of electrolyte resistance and film capacitance [ 54 ]. They also distinguish between capacitive and inductive hysteresis, associated with ion diffusion in the organic film, which manifest as counterclockwise and clockwise loops, respectively, in the transfer current [ 54 ]. Koch et al reproduced the forward–backward hysteresis curves by developing a drift–diffusion simulation model that incorporates an incomplete ionization approach, leveraging Poisson–Boltzmann statistics for accurate simulation of charge densities, and electrostatic properties of OECTs.…”
Section: Working Principle Of Oectsmentioning
confidence: 99%